PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN MODUL QT-BILINGUAL TERHADAP HASIL BELAJAR SISWA - Amalana, Husna; -, Sudarmin; -, Latifah (Jurnal Inovasi Pendidikan Kimia, 2013)
Quantum teaching learning model supported by QT(Quantum Teaching)-bilingual module emphasize optimization all multiple intelligences and learning style of students in learning activities with TANDUR frame. This research aimed to find out the effect of quantum teaching learning model supported by QT-bilingual module to the achievement of X grade students of SMA in Kedungwuni, how much the effect magnitude, and how student response. This research uses true experimental design with X.1 and X.8 classes as reasearch samples which determined by cluster random sampling technique. Data were collected through documentation, test, observation and questionnaire method. The results of hypothesis test analysis showed correlation and determination coefficient are 0.54 and 29.16%. The results of questionnaire stated that the students’ response is very good to quantum teaching learning model assisted by QT-bilingual module. Based on the analysis, it can be concluded that quantum teaching learning model assisted by QT-bilingual module effects on student learning outcomes by achieving the medium level of effect with contribution is 29.16%. Students’ response is very good actually to quantum teaching learning model supported by QT-bilingual module.Keywords: Quantum Teaching, QT-Bilingual Module